Sweating rate and dehydration levels in professional soccer players after an official league match (Spanish Second Division ``B´´) - Gomez Vera, G.; Del Valle Pascual, F. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
One of the main reasons of performance loss is the dehydration caused by inadequate liquid intake during physical exercise. When 2% total body weight is lost due to the fluid loss, this compromises many physiological and cognitive functions, resulting in a decrease in performance. In soccer, to determinate hydration strategies it is very important to maintain the proper water balance and avoid a performance fall. Our aim was to describe the sweating rate and the dehydration levels in professional soccer players after an official league match of the Spanish Second Division ``B´´.